Breaking Through the Zero Lower Bound - Agarwal, Ruchir (IMF Working Papers; Working Paper, 2015)
There has been much discussion about eliminating the 'zero lower bound' by eliminating paper currency. But such a radical and difficult approach as eliminating paper currency is not necessary. Much as during the Great Depression-when countries were able to revive their economies by going off the gold standard-all that is needed to empower monetary policy to cut interest rates as much as needed for economic stimulus now is to change from a paper standard to an electronic money standard, and to be willing to have paper currency go away from par. This paper develops the idea further and shows how such a mechanism can be implemented in a minimalist way by using a time-varying paper currency deposit fee between private banks and the central bank. This allows the central bank to create a crawling-peg exchange rate between paper currency and electronic money; the paper currency interest rate can be either lowered below zero or raised above zero. Such an ability to vary the paper currency interest rate along with other key interest rates, makes it possible to stimulate investment and net exports as much as needed to revive the economy, even when inflation, interest rates, and economic activity are quite low, as they are currently in many countries. The paper also examines different options available to the central bank to return to par when negative interest rates are no longer needed, and the associated implications for the financial sector and debt contracts. Finally, the paper discusses various legal, political, and economic challenges of putting in place such a framework and how policymakers could address them.